The Effect of Balance Exercise on Muscle Strength in the Elderly at UPT Panti Sosial Tresna Werdha Glenmore - Aprilyawan, Grenda; Makrup, Makrup; Wulandari, Enny; Waspada, Edy (Open Access Health Scientific Journal, 2025)
Background: The aging process causes a decline in musculoskeletal function, one of which is decreased muscle strength, which impacts balance and independence in older adults. Balance training is one physical intervention that can improve muscle strength in older adults. The purpose of this study was to determine the effect of balance exercise on muscle strength in older adults at the UPT Panti Sosial Tresna Werdha Glenmore. Methods: This study used a questionnaire-experimental design with a one-group pre-test and post-test approach. The sample consisted of 30 elderly people selected by total sampling. Muscle strength was measured using the Manual Muscle Testing (MMT) instrument before and after the intervention. Data were analyzed using the Wilcoxon test.Results: Before the intervention, most elderly people had mild muscle strength (76.7%). After the balance exercise intervention, the majority of elderly people experienced an increase in muscle strength to the normal category (73.3%). The Wilcoxon test results showed a P-value of 0.000 (<0.05), indicating a significant effect of balance exercise on muscle strength in elderly people.Conclusion: Balance exercise significantly improves muscle strength in older adults. This intervention can be implemented as a routine exercise program to improve physical function and quality of life in older adults.